Los dilemas del Estado peruano en la implementación y aplicación de la Ley de Consulta Previa en los Andes peruanos - Barrio de Mendoza, Rafael (2013)
The Peruvian government enacted a new law granting consultation rights to indigenous peoples as a mechanism to enhance social inclusion in the country. The law generated debates about the criteria to identify indigenous population in the Andean region. Why does this law have problems granting consultation rights to Andean people? This paper aims to answer the question by reviewing historically the different Andean identities and analyzing the current international debate on indigenity. Our main argument is that the government intrying to apply the law is structuring a restrictive model that is hardlyable to grasp the complexity and dynamism of Andean identities.